2020
DOI: 10.1155/2020/3584030
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Assessment of Temperature Data Products for the Detection of Warming Trends and Abrupt Transitions over the Largest Irrigated Area of Pakistan

Abstract: Reliable and accurate temperature data acquisition is not only important for hydroclimate research but also crucial for the management of water resources and agriculture. Gridded data products (GDPs) offer an opportunity to estimate and monitor temperature indices at a range of spatiotemporal resolutions; however, their reliability must be quantified by spatiotemporal comparison against in situ records. Here, we present spatial and temporal assessments of temperature indices (Tmax, Tmin, Tmean, and DTR) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Recent increased frequency of unpredictable occurrences of rainfall impacted rice, maize, wheat, sugarcane, and cotton production along with other minor crops, such as millet, vegetables, and tree fruits, including citrus and mango in the central Punjab districts, including Nankana Sahib, Sialkot, Gujranwala, Hafizabad, Sheikhupura, and Sargodha [33]. This region is fairly vulnerable to climate change because of the large variety and intense events that occur during the summer and winter monsoon precipitation seasons [34][35][36][37][38]. Spatial and temporal evaluation of the GPPs (gridded satellite precipitation products) is vital to examine in-depth hydro-meteorological scenarios across the study region, where observed data are inadequate.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent increased frequency of unpredictable occurrences of rainfall impacted rice, maize, wheat, sugarcane, and cotton production along with other minor crops, such as millet, vegetables, and tree fruits, including citrus and mango in the central Punjab districts, including Nankana Sahib, Sialkot, Gujranwala, Hafizabad, Sheikhupura, and Sargodha [33]. This region is fairly vulnerable to climate change because of the large variety and intense events that occur during the summer and winter monsoon precipitation seasons [34][35][36][37][38]. Spatial and temporal evaluation of the GPPs (gridded satellite precipitation products) is vital to examine in-depth hydro-meteorological scenarios across the study region, where observed data are inadequate.…”
Section: Study Areamentioning
confidence: 99%
“…Additionally, anthropogenic activities, such as industrial growth, infrastructural activities, urbanization, and global increasing air temperature are also liable [38]. In Phase-2, annually, rainfall increased by 19%, which can be ascribed to the increasing tendency towards extreme events and huge temperature gradients, resulting in rapid land-ocean interactions [11,71,72].…”
Section: Variability and Trends In Rainfallmentioning
confidence: 99%
“…Therefore, to ensure the data quality, 40 synoptic stations for which the long‐term daily climate records are available (i.e., less than 5% missing data) have been chosen across AEZs of Pakistan (Figure 1 and Table S1). The usage of gridded data in complex landscapes creates uncertainties in results and affects long‐term climate trends (Baudouin et al, 2020; Dahri et al, 2021; Nawaz et al, 2020). Hence, this work used observational data of high quality with adequate coverage (i.e., space and time) within AEZs of Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed descriptions of selected meteorological stations are given in (Table S1 in Supporting Information S1 ). The use of gridded climate products in complex terrain produces uncertainties in results, which may affect the long‐term trend of climate variables (Baudouin et al., 2020 ; Dahri et al., 2021 ; Nawaz et al., 2020 ). Therefore, in this study, we make use of high‐quality observational data with sufficient spatial and temporal coverage across AEZs of Pakistan.…”
Section: Methodsmentioning
confidence: 99%